Legislativos municipais: tensões entre representação e participação - Teixeira, Luiza Reis (2016)
The present research work presents a theoretical-empirical reflection about the relation between political representation and social participation within the contemporary theory of Democracy. The main issue addressed here relates to the participant mechanisms and institutions that emerged in the recent Brazilian democratic context shaped in the form of deliberative spaces influencing decision-making processes. We have adopted, thus, a concept of the political representation theory that conceives representation dynamically, based on communication relating governmental agents and institutions and society. Therefore, on the theoretical level, the relation between the existing political representation and social participation is discussed. The objective of this research consists in analyzing how social participation mechanisms function in Brazil, particularly in the Legislative Power, on the local level, by means of examining their participative potential within the context of the Legislature Houses of the cities of São Paulo and Salvador. For this, we have parted from Vera’s (2012) data analysis methodological proposal, which focuses on the architecture of participation, grounded on the description of experiences from a structural language frame. The analytical framework is developed in three different levels of abstraction: macro, intermediate and micro, to which we dedicated three analytical statements. The macro level presents participant institutions from a historical perspective, the institutional architecture of Councils and Conferences, and proposes a model to represent them. The intermediate analytical level deals with the functioning of participative mechanisms in the Legislative Power, from a comparative perspective with Executive Power mechanisms, pointing some conclusions on participation in municipal legislatures in Brazil. The micro level analyses the operation of participative mechanisms in two different contexts: The Municipal Houses of the cities of São Paulo and Salvador. Finally, based in the empirical findings, we present an analysis of representation and participation theories. Final results highlight the need for a more comprehensive articulation of representation and participation theories, as a way of thinking over the existing institutions. Presently, whereas Executive Power has a well-structured participative institutional architecture, with several different institutions, in Legislature Power, these mechanisms function in isolated form, and are not reproduced in different federation spheres. Internal factors – as administrative structure and political interest, as well as external factors – as pressures from civil society organized sectors interfere in the participative potential of participant mechanisms in the two houses analyzed.